A Smart Accounting System for Real-Time Mosque Financial Fund Management Based On Android and Web Mobile through The Implementation of The Agile Development Scrum Method: (Case Study: The Baiturrahim Mosque is Located in Uteun Bayi Village, Banda Sakti District, Lhokseumawe City) - Ardian, Zalfie; Abdullah, Dahlan; Bintoro, Andik; Yusra, Muhammad; Akbar, Abdul Hanif; Lubis, Fauzan Arbi (PT Mattawang Mediatama Solution, 2024)
The Smart Accounting System (SAS) is an accounting system that optimizes the financial administration of an entity or company by utilizing artificial intelligence and information technology to streamline the accounting process. Mosques may encounter a variety of financial challenges; among these are fund management, income, and expenses. Distrust among the congregation may result from a lack of transparency in mosque financial management. Consequently, it is crucial to preserve transparency and furnish transparent financial statements. In order to resolve these financial challenges, it is crucial to implement effective financial management, establish a realistic budget, enhance transparency, and engage the congregation in the mosque's financial management. The Agile Development Scrum method is employed to design the Smart Accounting System, which is based on Android mobile and web. The Agile approach enables the team to effortlessly adjust to changes during the development process, as it fosters congregational engagement throughout the entire development cycle. The mosque treasurer or finance team's participation is indispensable in the context of the Smart Accounting System to guarantee that the appropriate requirements are satisfied. Agile ensures superior system quality by emphasizing continuous testing and feedback from the mosque congregation. The proper location for field studies and initial data sources for the development of the Smart Accounting System is Baiturrahim Mosque, located in Uteun Bayi Village, Lhokseumawe City. Additionally, the Agile Scrum methodology will be implemented to execute the system design. The subsequent phase involves the implementation of the Black Box system testing method and User Acceptance Testing (UAT)